Educational Role on Dakwah Qur'anic Approach in Human Development - Abdul Ghafar Haji Don (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2005)
Al-Qur'an as a guidance book is the authentic and authoritic educational Sources. It is importance to use Al-Qur'an as a main source of Moslem. This article explains the educational role of dakwah from Quranic point of view in human development It will explains five educational approaches on Al-Qur'an, they are: bi al-maurizah (education through advice), tarbiah bi al- Qissah (education through story telling), tarbiah bi al-ahdath (education through action), tarbiah bi af-cuqubah (education through law enforcement dan tarbiah bi al-Qudwah (education through example) The writer concludes that the five aspects of educational dakwah from Al-Qur'an would be able to fulfill human development